EFFECTS OF FINANCIAL AND TAX INCENTIVES ON INDUSTRIAL INVESTMENTS (Third Sector Social Economic Review, 2022)
Countries question the effectiveness of fiscal incentives as a determinant for attracting foreign direct investment. In the article, tax incentives and usage targets, the effects of other financial incentives on the industry and how capital stock, production capacity, depreciation exemption and taxes affect investment according to the prepared model are examined. Countries aim to offer these incentives for certain sectors. All data were collected from Iran Statistical Center and Central Bank database. Panel econometric technique (EGLS) according to the weighted least squares method; It has been used in the steel, petrochemical, cement, automobile, textile, tile and ceramics, food industries. Excel custom software was used to process, categorize and prepare the variables and enter them into the Eviews software. Finally, Eviews software was used to predict the model and test the article hypotheses. According to the results, all article hypotheses were accepted; the tax credits variable has a positive effect on the investment index in different sectors of the industry. It shows the negative impact of investment cost on investment in various sectors of industry. Tax incentives affect investment and costs, income per capita, cost of capital use, available capital and production capacity. The depreciation exemption affects the effective tax rate.
Keywords: Iran; Financial Incentives; Tax Incentives; Investment Decisions; Investment Incentives